Improving problem solving ability in mathematics using active learning strategy type learning starts with a question - M Handayani; E Herlina; K Rahm; K Yulianti (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
This study aims to look at improvements and investigate the difference between students’ mathematics problem solving ability using Active Learning Strategy Type Learning Starts With a Question (LSQ) and using direct learning. This research was a quasi-experiment by randomized pretest-posttest control group design to 48 students of junior high school in Sumatra Barat in the even semester of 2017. Methods of data collection in this study observation, documentation and test. N-Gain and T test was used to analyzed the data. Results showed that there was an increase in students' mathematics problem solving abilitiy with high categories and mathematics problem solving ability of students using LSQ strategy were better than students' mathematics problem solving ability using direct learning.